Ghrelin secretion in humans – a role for the vagus nerve?. Issue 6 (2nd February 2018) - Veedfald, S.; Plamboeck, A.; Hartmann, B.; Vilsbøll, T.; Knop, F. K.; Deacon, C. F.; Svendsen, L. B.; Holst, J. J.
Abstract: Background: Ghrelin, an orexigenic peptide, is secreted from endocrine cells in the gastric mucosa. Circulating levels rise in the preprandial phase, suggesting an anticipatory or cephalic phase of release, and decline in the postprandial phase, suggesting either the loss of a stimulatory factor or inhibition by factors released when nutrients enter the intestine. We hypothesized that vagal signals are not required for the (i) preprandial increase or (ii) postprandial suppression of ghrelin levels. Further, we wanted to investigate the hypothesis that (iii) glucagon‐like peptide‐1 might be implicated in the postprandial decline in ghrelin levels. Methods: We measured ghrelin levels in plasma from sham‐feeding and meal studies carried out in vagotomized individuals and controls, and from a GLP‐1 infusion study carried out in fasting healthy young individuals. Key Results: We find that (i) ghrelin secretion is unchanged during indirect vagal stimulation as elicited by modified sham‐feeding in vagotomized individuals and matched controls, (ii) ghrelin secretion is similarly suppressed after meal ingestion in vagotomized individuals and controls, and (iii) infusion of GLP‐1 does not lower ghrelin levels. Conclusions & inferences: We conclude that for postprandial suppression of circulating ghrelin levels, a circulating factor (but not GLP‐1) or short (duodeno‐gastric) reflexes seem to be implicated. Abstract : Vagal stimulation does not acutely increase or decrease ghrelin levels and vagal innervation is not necessary for the decline in ghrelin after food intake. Atropine but not GLP‐1 suppresses ghrelin levels.